THE RESULTS OF LONG-TERM PAH-SPECIFIC MONOTHERAPY WITH BOSENTAN IN PATIENTS WITH IDIOPATHIC PULMONARY HYPERTENSION - V. M. Paramonov; T. V. Martynyuk; N. M. Danilov; Yu. G. Matchin; I. Ye. Chazova (Евразийский Кардиологический Журнал)
Objective. To evaluate the dynamics of clinical and functional status, the parameters of central hemodynamics and tolerability of bosentan therapy lasting more than 12 months in patients with idiopathic pulmonary hypertension (IPAH). Materials and methods. In the study we included 20 IPAH non-responders with functional class II-III (WHO). All patients were assigned to treatment with bosentan in the initial dose of 125 mg/ day, which was increased to 250 mg/day after 4 wks. The mean FU duration was 15±3 months. Conducted 5 visits: at baseline and visit 5, all patients underwent a comprehensive examination, including right heart catheterization (RHC). Transthoracic echocardiography was performed additionally at visit 3. 6-minute walking (6MW) test was assessed every 3 months. For safety reasons hepatic transaminases were analyzed monthly. Results. Bosentan therapy resulted to significant improvement of functional class (FC (I/II/III) with 0%/45%/55% to 30%/45%/25%, p